2015
DOI: 10.1017/s0007114515002779
|View full text |Cite
|
Sign up to set email alerts
|

Lutein intake at the age of 1 year and cardiometabolic health at the age of 6 years: the Generation R Study

Abstract: Lutein is a carotenoid with strong antioxidant properties. Previous studies in adults suggest a beneficial role of lutein on cardiometabolic health. However, it is unknown whether this relation also exists in children; therefore, we aimed to assess the relation between lutein intake at 13 months of age and cardiometabolic outcomes at the age of 6 years. We included 2044 Dutch children participating in a population-based prospective cohort study. Diet was measured at 13 months of age with an FFQ. Lutein intake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
(77 reference statements)
0
5
0
Order By: Relevance
“…Lack of lutein effect on cognitive performance may be caused by selection of well-nourished population, whereas largest functional effects of lutein may be the most significant for those with relative deficiency; selection poor biomarker (plasma concentration) for lutein in brain (MOPD would be better), as well probably not the most sensitive cognitive tests for measuring the effects of diet on brain development [ 178 ]. The Generation R Study ( n = 2044 healthy Dutch children) did not support the hypothesis that lutein intake in early life (13 months of life) has beneficial role for later cardiometabolic health, anthropometrics and body measures at the age of six [ 179 ].…”
Section: Carotenoids and Infant Health And Developmentmentioning
confidence: 99%
“…Lack of lutein effect on cognitive performance may be caused by selection of well-nourished population, whereas largest functional effects of lutein may be the most significant for those with relative deficiency; selection poor biomarker (plasma concentration) for lutein in brain (MOPD would be better), as well probably not the most sensitive cognitive tests for measuring the effects of diet on brain development [ 178 ]. The Generation R Study ( n = 2044 healthy Dutch children) did not support the hypothesis that lutein intake in early life (13 months of life) has beneficial role for later cardiometabolic health, anthropometrics and body measures at the age of six [ 179 ].…”
Section: Carotenoids and Infant Health And Developmentmentioning
confidence: 99%
“…Additionally, articles where the score calculated was non‐continuous ( n = 8) and articles where the score was measured at adolescence or adulthood ( n = 58) were excluded. A total of 91 articles met the review criteria and were included in the data extraction .…”
Section: Resultsmentioning
confidence: 99%
“…The AREDS2 study found that L supplementation was unable to reduce CV diseases in patients with AMD [ 168 ]. Leermakers et al assessed median L intake in 13-month-old children by administering a food frequency questionnaire to their caregivers but, at 6 years of age, they did not find any improvement in cardiometabolic health [ 169 ], suggesting a lack of correlation between L consumption and parameters of CV health. However, a recent meta-analysis by the same authors that included studies enrolling more than 350,000 participants concluded that L consumption is associated with better CV health [ 170 ].…”
Section: Extra-eye Actionsmentioning
confidence: 99%